Shari’ah court’s decision and respondent’s view on child custody after divorce in Kuala Lumpur and Selangor - Akbar Kamarudin @ Abdul Shukor (Penerbit Universiti Kebangsaan Malaysia, 2022)
The importance of child custody after divorce in family law is evident. The important issues in child custody include the best interest of the child, custody arrangements, the residence of the child, contact arrangements, parental responsibility for the child, and child maintenance. Islamic law through the Shari’ah court, in general, have to determine the issues based on specific principles. This article examines empirical research on the Shari’ah court’s decisions and the selected respondents’ views in Kuala Lumpur and Selangor, Malaysia. In the court, the research analysed 103 selected court cases. On the other hand, the research also involved two children of divorce. Several patterns were derived from the research namely: (a) the preference of sole custody over joint custody, (b) the preference of the mother over others in the residence of the child, (c) the recognition of the joint residence of the child, (d) the recognition of joint contact apart from sole contact, (e) the recognition of joint parental responsibility for the child, and (f) the award of child maintenance. The most important thing extracted from the pattern was the role of mutual consent in determining child custody. Thus, mutual consent will influence the party to adopt a harmonious way of settling their disputes.